(3JYdjb Ydi GdeDKQGJ heaJGM GdeTcdGJs - (3Ydj Hf eMeO Hf CMeO GdHcQis; (3CHh eMeO GdMSf Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B584 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3bGd GdTjN GdQUGU GdMeO ddg NGdb GdCQVjf hGdSeGhGJ GdMeO gh GdKfGA GdMSf , hjbGd dg CjVkG eOMkG Ch GdeOM CYe s
(3BNQgG (B:s
(3agPg WQjbI Gdbhd ai MbGFb GdeDKQGJ hbO HjfG GdcdGe ai Pdc Ydi WQjbI GdELeGd Je gPG GdeNJUQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV GdcdeGJ HGdCShO GdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJhMjO hGdedd hGdfMds